SUMOylation by SUMO2 is implicated in the degradation of misfolded ataxin-7 via RNF4 in SCA7 models - Marinello, Martina; Werner, Andreas (Disease models & mechanisms, 2019)
Perturbation of protein homeostasis and aggregation of misfolded proteins is a major cause of many human diseases. A hallmark of the neurodegenerative disease spinocerebellar ataxia type 7 (SCA7) is the intranuclear accumulation of mutant, misfolded ataxin-7 (polyQ-ATXN7). Here, we show that endogenous ATXN7 is modified by SUMO proteins, thus also suggesting a physiological role for this modification under conditions of proteotoxic stress caused by the accumulation of polyQ-ATXN7. Co-immunoprecipitation experiments, immunofluorescence microscopy and proximity ligation assays confirmed the colocalization and interaction of polyQ-ATXN7 with SUMO2 in cells. ...
Gesehen am 16.05.2019